Facies analysis, depositional activity, and internal structure of sieve deposits on an active alluvial fan. Issue 3 (9th December 2022) - Novak, Andrej; Vrabec, Marko; Popit, Tomislav; Vižintin, Goran; Šmuc, Andrej
Abstract: Sieve lobes typically appear in gravel‐rich and matrix‐poor alluvial fans. Despite being extensively studied, the sieve‐lobe facies has been defined largely based on qualitative field observations without quantitative sedimentological analyses. Additionally, depositional activity of sieve lobes has not been monitored over extended periods (monthly to annually) and not directly associated with specific precipitation triggers. Furthermore, the internal geometry of sieve‐lobe built alluvial fans has not yet been imaged by subsurface methods. We performed a multi‐method analysis of sieve lobes in the Julian Alps (NW Slovenia) on an alpine alluvial fan composed of carbonate gravels. We performed a detailed textural and structural sedimentological analysis of 11 recent sieve lobes differing in size and age. A three‐year aerial survey of the alluvial fan surface with a small unmanned aircraft and photogrammetric modelling was used to detect active sieve‐lobe evolution. Detected sieve‐lobe formation events and volumetric surface changes were paired with triggering precipitation events. Ground‐penetrating radar (GPR) profiling depicted the geometry of the sieve‐lobe built alluvial fan. The sieve‐lobe facies consists of over 80% poorly sorted, open‐framework gravels and less than 2% mud. Lobes exhibit downward coarsening and increase in clast mean size. These textural and structural characteristics are present in all sieve lobes regardless of their age and size. Sieve lobes form with a sub‐annual frequency, usually following 24 h rainfall events exceeding 50 mm. Over 1000 m 3 of sediment was deposited during these events. The GPR profiles confirm that the studied alluvial fan is formed predominantly by stacked sieve lobes. Quantitative sedimentary analysis of sieve lobes, monitoring of their recent evolution, and depiction of their subsurface geometry—demonstrated in this study—reinforce the challenged concept that sieve lobes are one of the main building blocks of alluvial fans. This work also demonstrates that, under specific conditions, sieving may become the dominant alluvial fan‐forming process. Abstract : We performed a detailed sedimentological analysis of 11 sieve lobes on an active alluvial fan. A three‐year aerial surface survey detected active sieve‐lobe evolution, which was paired with triggering precipitation events. Ground‐penetrating radar depicted the architecture of the sieve‐lobe built alluvial fan. Lobes exhibit downward coarsening and increased clast mean size. They are deposited annually during rainfalls exceeding 50 mm, during which more than 1000 m 3 of sediment was deposited. Gravel‐rich and matrix‐poor alluvial fans can be almost entirely sieve‐lobe built.